Immunologic changes in the peripheral blood transcriptome of individuals with early-stage chronic Chagas cardiomyopathy: a cross-sectional studyResearch in context - Carolina Duque; Jaime So; Yagahira E. Castro-Sesquen; Kelly DeToy; Sneider A. Gutierrez Guarnizo; Fatemeh Jahanbakhsh; Edith Malaga Machaca; Monica Miranda-Schaeubinger; Indira Chakravarti; Virginia Cooper; Mary E. Schmidt; Luigi Adamo; et al. (The Lancet Regional Health. Americas)
Summary: Background: Chagas disease, caused by the protozoan parasite Trypanosoma cruzi, is a neglected disease that affects approximately 6 million individuals worldwide. Of those infected, 20–30% will go on to develop chronic Chagas cardiomyopathy (CCC), and many ultimately to advanced heart failure. The mechanisms by which this progression occurs are poorly understood. In this exploratory study, we sought to provide insight into the physiologic changes associated with the development of early CCC. Methods: We used RNA sequencing to analyse the gene expression changes in the peripheral blood of six patients with Chagas disease with early structural heart disease, four patients with Chagas disease without any signs or symptoms of disease, thirteen patients without Chagas disease with early structural heart disease, and ten patients without Chagas disease or signs of heart disease. Pathway analyses and immune cell deconvolution were employed to further elucidate the biological processes underlying early CCC development. Findings: Our analysis suggests that early CCC is associated with a downregulation of various peripheral immune response genes, including changes suggestive of reduced antigen presentation and T cell activation. Notably, these genes and processes appear to be distinct from those of non-Chagas cardiomyopathies. Interpretation: This work highlights the potential importance of the immune response in early CCC, providing insight into the early pathogenesis of this disease and how it may differ from other cardiomyopathies. The changes we have identified may serve as biomarkers of early CCC and could inform future longitudinal cohort studies of markers of disease progression and strategies for the treatment of CCC in its early stages. Funding: NIH, FONDECYT, IDSA, NSF.